2014
DOI: 10.1039/c4cc01944j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic asymmetric aminolactonization of 1,2-disubstituted alkenoic acid esters: Efficient construction of aminolactones with an all-carbon quaternary stereo-centre

Abstract: Chiral BOX-Cu(OTf)2 catalyzed enantioselective aminolactonization of the tert-butyl ester of alkenoic acids has been developed via in situ aziridination using PhINNs as the nitrene source. It provides exclusively trans-γ- and δ-amino lactones including an additional all-carbon quaternary stereo-centre with up to 98% ee in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…However, the chemistry of spiroaziridine oxindoles has not been explored yet. Our continued interest in aziridine chemistry , and recent research in oxindoles led us to hypothesize that chiral spiroaziridine oxindoles could be opened up stereoselectively by carbon nucleophiles like indoles to produce nonracemic 3,3′-bisindoles bearing all-carbon quaternary stereogenic centers. This remains one of the fascinating research areas in modern organic synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the chemistry of spiroaziridine oxindoles has not been explored yet. Our continued interest in aziridine chemistry , and recent research in oxindoles led us to hypothesize that chiral spiroaziridine oxindoles could be opened up stereoselectively by carbon nucleophiles like indoles to produce nonracemic 3,3′-bisindoles bearing all-carbon quaternary stereogenic centers. This remains one of the fascinating research areas in modern organic synthesis.…”
mentioning
confidence: 99%
“…Pathway A involves a direct S N 2 mechanism (intermediate A ), pathway B proceeds through the indolone intermediate B , and pathway C involves anchimeric assistance via the formation of a α-lactum-type aziridinone intermediate C . The direct S N 2 pathway is expected to afford an inversion of configuration. , Moreover, this pathway is unfavorable due to excess steric crowding at the stereocenter. On the other hand, if the reaction goes through the indolone intermediate, it will definitely produce racemic bisindoles.…”
mentioning
confidence: 99%
“…Using Cu(OTf) 2 and ligand 600e the aziridination proceeds smoothly and upon treatment with additional Cu(OTf) 2 or silica gel the aziridine successfully cyclizes to produce the desired aminolactone 748 in up to 98% ee . 277 …”
Section: Bis(oxazoline) Ligandsmentioning
confidence: 99%
“…Our research experiences in the ring-opening reaction of aziridines and spiroaziridine oxindoles led us to wonder whether chiral spiroaziridines 1 could undergo a stereocontrolled NuF reaction with fluoride at the spirocenter (sp 3 -tertiary carbon). It has been previously revealed that N -sulfonyl spiroaziridines 1 are activated by the H-bonding of surface water for the stereocontrolled nucleophilic ring opening with neutral nucleophiles, and water-miscible nucleophiles undergo slow reaction with poor stereoselectivity.…”
mentioning
confidence: 99%